The relative strength of the most important oriental religions and their influence on Roman life up to the end of the third century, A.D. - Van Rensburg, J. P. J.(Johannes Petrus Jansen),1911-1980 (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Litt.) -- University of Stellenbosch, 1943.